Patient-specific hemodynamics modeling of carotid artery stenosis in a swine model based on 3D rotational angiography. (September 2021) - Yao, Qinghe; Zhu, Hongkun; Wang, Weizhu; Shen, Yongting; Liu, Zhong; Wang, Jinshan; Shi, Zhongsong
Highlights: In vivo DSA image and reconstruction for 3D modeling of swine model, eight minis-wines were used to develop carotid atherosclerosis with intervention for in vivo experiment purpose. Validation of the empirical function of WSS for swine model. Two numerical models based on different wall functions were compared, and the blood flow pattern was discussed based on simulation results. Newly proposed swine blood flow high-order expression and carotid vessel model with stenosis. Abstract: Carotid stenosis is a common physiological abnormality that can cause a stroke or even death. For a clear understanding of its forming mechanism and potential damage, a hemodynamics model of carotid artery stenosis in a swine is built and analyzed based on surgery and ultrasonography. Eight Chinese mini-swine were partially ligated; transcranial Doppler and 3D DSA are employed to obtain physiological parameters for reconstructing the in vivo experimental vessel model. A numerical model of the swine blood flow and a detailed swine carotid vessel model with stenosis are proposed. The empirical function of WSS was validated for the swine model. Two models, a rigid wall and an elastic wall are precisely compared for pathological analysis of vascular diseases, such as carotid atherosclerosis and hemangioma. The elastic wall model performs better in representing experimental conditions while the rigid wall is much more efficient. Both models show that stenosis has a significant effect on resulting complex blood flow behavior and concentrated WSS distribution.